TRACDUINO PLATFORM CAPABILITIES (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
Using the Tracduino platform, which is considered one of the platforms used to control existing robots in the field of robotics, getting to know its features and capabilities.